Experimental Simulation of Burial Diagenesis and Subsequent 2D-3D Characterization of Sandstone Reservoir Quality - Charlaftis, Dimitrios; Dobson, Katherine J.; Jones, Stuart J.; Lakshtanov, Dmitry; Crouch, Jonathan; Cook, Jennie (Frontiers in Earth Science, 2022)
Characterization of deeply buried sandstones and their reservoir quality is of paramount importance for exploring, developing, and subsurface storage of energy resources. High reservoir quality in deeply buried sandstones is commonly correlated with the occurrence of grain coatings that inhibit quartz cementation. The development of reliable models that can predict reservoir quality relies on incorporating quantitative understanding of these diagenetic processes. Hydrothermal experiments simulating burial diagenesis were integrated with multi-scale X-ray tomography to quantify the 3-dimensional evolution of grain coating volume and porosity with increasing temperature; while microscopic and automated quantitative mineralogy analysis were used to track the associated mineralogical alterations. To simulate reservoir evolution, sandstone samples from the Lower Jurassic Cook Formation (Oseberg Field, 30/6-17R, Norway) were exposed to a silica supersaturated Na2CO3 (0.1 M) solution for up to 360 h at temperatures of 100–250°C. The experimental results show the main porosity and permeability reduction window is associated with pore-filling kaolinite, and lies between 150 and 200°C, above which little change occurs. Volumetric increases in grain coating start to occur at ∼150°C through precipitation of authigenic chlorite, and continue to 250°C, irrespective of the experimental duration. Together with preexisting siderite coatings, the newly precipitated chlorite prevents the loss of reservoir quality by inhibiting quartz overgrowth development. Pore flow simulations based on the observed temperature-dependent 3-dimensional pore networks allow us to characterize pore-throat and permeability evolution and gain quantitative understanding of the impact of diagenetic overprinting on deeply buried sandstone reservoirs.